2008
DOI: 10.1002/hed.20876
|View full text |Cite
|
Sign up to set email alerts
|

Survivin and epidermal growth factor receptor expression in surgically treated oropharyngeal squamous cell carcinoma

Abstract: Considering the strong impact of nuclear survivin expression on survival, the survivin expression should be prospectively evaluated to select patients with an increased risk for disease recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…In our study, we found survivin expression in different levels was significantly increased in OSCC tissue, which was consistent to previous studies (Preuss et al, 2008;De Maria et al, 2009;Khan et al, 2009;Halasova et al, 2012). In peritumoral tissue that appeared normal with naked eye, we found both survivin mRNA and protein expression level increased comparing to normal controls when detected by qRT-PCR and ELISA respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we found survivin expression in different levels was significantly increased in OSCC tissue, which was consistent to previous studies (Preuss et al, 2008;De Maria et al, 2009;Khan et al, 2009;Halasova et al, 2012). In peritumoral tissue that appeared normal with naked eye, we found both survivin mRNA and protein expression level increased comparing to normal controls when detected by qRT-PCR and ELISA respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, some authors hypothesized that cytoplasmic survivin expression is responsible for poor prognosis and for the resistance to therapy in oral squamous cell carcinoma (31). Although effects of nuclear vs. cytoplasmic expression of survivin are still ambiguous, some investigators have reported that predominantly nuclear survivin over-expression is a negative prognostic factor in oropharyngeal squamous cell carcinomas (32). We observed both nuclear and cytoplasmic survivin expression in all cases in varying proportion.…”
Section: Discussionmentioning
confidence: 47%
“…Expression of survivin, an apoptosis inhibitor targeting caspase 3 and caspase 7, was found elevated in OSCC tissue 71, 72, whereas caspase 3 expression level is decreased 72. Consistently, caspase 3 is found associated with a favorable prognosis for primary resected ESCC patients 73, whereas survivin expression was proposed as negative prognostic factor of OSCC 74. However, different roles of caspase 3 in OSCC are also suggested.…”
Section: Notch Signaling In Head and Neck Squamous Cell Carcinoma (Hnmentioning
confidence: 85%